EFECTOS DE LAS MEDIDAS DE PROTECCIÓN FRENTE A LA VIOLENCIA CONTRA LA MUJER EN LA PROVINCIA DE TRUJILLO, DEPARTAMENTO LA LIBERTAD: 2009-2018 - García García, Manuel Jesús (2018)
The present investigative work arose when he was making support to Judge Miguel Ángel Chávez of the Third Magistrate Court in Lima North specialized in Faltas and had the opportunity to project sentences, it is in this circumstance that the judge was observed to order in his judicial resolutions the measure of conduct that the defendant approaches the court to sign monthly and pay a compensation for the damage caused to the woman victim of violence. In addition to the above, daily in the media is disseminated news regarding the increase in cases of violence against women, such that the Minister of Women and Vulnerable Populations, Ana María Mendieta, reported that from January to June of 2018 there have been 69 femicides. The alarming figure would show a 40% increase in those killings compared to the cases registered in the same period of months during the past year. Faced with this problem began to investigate judicial decisions issued by family judges on violence against women in the family in the city of Trujillo, La Libertad department with the aim of raising the hypothesis that is what It is happening so that violence against women increases. In this sense, after analyzing and confronting these judicial decisions with reality, the following hypothesis arose: If the judge does not fully apply the protective measures provided for in the law on family violence, this could be a cause that would contribute to an increase in cases of violence against women. In addition, due to what is stipulated in the regulations of the University that to present a thesis must be presented and defended before a jury with arguments, it is for this reason, that judicial remedies in matters of family violence were collected as evidential means for their timely lift. Finally, it is for this reason that this thesis aims to prove that the inefficient application of protection measures could be a cause that contributes to the increase in cases of violence against women and its aggravating the crime of femicide and attempted in the period 2009-2018. Keywoards: Judicial resolutions, protection measures, increase of cases,violence against women, crime of feminicide.